Ordinary Jerusalem, 1840-1940 Opening New Archives, Revisiting a Global City - Dalachanis, Angelos; Lemire, Vincent (Open Jerusalem, 2018)
In Ordinary Jerusalem, Angelos Dalachanis, Vincent Lemire and thirty-five scholars depict the ordinary history of an extraordinary global city in the late Ottoman and Mandate periods. Utilizing largely unknown archives, they revisit the holy city of three religions, which has often been defined solely as an eternal battlefield and studied exclusively through the prism of geopolitics and religion. At the core of their analysis are topics and issues developed by the European Research Council-funded project "Opening Jerusalem Archives: For a Connected History of Citadinité in the Holy City, 1840-1940." Drawn from the French vocabulary of geography and urban sociology, the concept of citadinité describes the dynamic identity relationship a city's inhabitants develop with each other and with their urban environment.